A survey of public preferences on patterns of Terengganu Batik for digital exhibitions - Firdaus, Amir; Che Din, Sharkawi (Universiti Teknologi MARA, Perak, 2025)
Batik is one of Malaysia’s most valued cultural heritages, yet public engagement particularly with regional variations such as Terengganu Batik remains limited. Despite its artistic significance, modern audiences often overlook its traditional value due to limited exposure, changing design preferences, and underutilisation of digital presentation methods. This study aimed to explore public preferences toward Terengganu Batik patterns and their potential to be showcased through digital exhibitions that incorporate interactive and immersive elements. A quantitative approach was adopted through an online questionnaire, distributed to Malaysian respondents aged 18 years old and above. The survey collected data on Batik familiarity, motif and color preferences, and interest in digital exhibition formats. A total of 121 valid responses were gathered, exceeding the recommended sample size based on Cohen’s sample size table. Findings revealed that while most participants were familiar with Batik in general, fewer recognised the uniqueness of Terengganu Batik. Respondents preferred floral patterns and pastel tones and expressed strong interest in digital exhibition features such as storytelling, ambient sound, and interactive projections. The study concluded that aligning Batik design with public preferences and presenting it through immersive digital formats may enhance cultural appreciation and ensure its continued relevance.